Investigação de Casos de Coqueluche na Direção Regional de Saúde XVIII - Ribeirão Preto, 2004/2005 - Guedes Pellini, Alessandra Cristina; Marques Pinto Carvalhanas, Telma Regina; Ciccone, Flávia Helena; de C. J. O. Sidi, Maria Stella (BEPA. Boletim Epidemiológico Paulista, 2005)